Sources and types of information on self-care symptom management strategies for HIV and AIDS - Regis R. Marie Modeste; Sisana J. Majeke (AOSIS, 2014)
Background: It has been reported that South Africa has the highest number of people living with HIV worldwide, with more women being infected than men. Women living with HIV have been documented as experiencing various symptoms related to HIV and use various strategies to manage these symptoms. Objective: The objective of this study was to explore the sources and types of information regarding self-care symptom management strategies received by women living with HIV. Method: The study was conducted at an HIV clinic in an urban area of KwaZulu-Natal. Individual in-depth interviews were completed with 11 women who were living with HIV,exploring the sources of information received on how they manage the HIV- (and/or AIDS-) related symptoms they experienced as well as the types of information received. The collecteddata were analysed using qualitative content analysis. Results: The participants identified various sources, which mainly included groups of people who provided them with information on how to manage their HIV-related symptoms, namely healthcare providers, their personal networks and the community. The different sources offered different types of information, including the use of medication, complementary treatments and self-comforting activities. Conclusion: The study highlights that participants used multiple sources to get information about how to manage the experienced symptoms related to HIV, namely, healthcare providers, family and friends as well as themselves. It is to be noted that each source provided a preferred type of information.